2021
DOI: 10.4081/aiua.2021.4.436
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between renal scarring and neutrophil-to-lymphocyte ratio in patients with vesicoureteral reflux?

Abstract: Objectives: Vesicoureteral reflux (VUR) exacerbates the risk of renal scarring by establishing a ground for pyelonephritis. It is known that the inflammatory process is more influential than the direct damage caused by bacterial infection in the development of renal scars after pyelonephritis. Therefore, the present study aims to investigate the relationship between renal scarring and systemic inflammatory markers in patients with VUR.Material and methods: Hundred and ninety-two patients (116 females, 76 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This has led researchers to investigate other factors. In recent years, inflammatory markers have played an important role in predicting the prognosis of malignancy, cardiovascular diseases, scar development in vesicoureteral reflux and rheumatic diseases [7,8]. In the present study, we focused on whether pre-operative haematological parameters affected UCF development.…”
Section: Discussionmentioning
confidence: 96%
“…This has led researchers to investigate other factors. In recent years, inflammatory markers have played an important role in predicting the prognosis of malignancy, cardiovascular diseases, scar development in vesicoureteral reflux and rheumatic diseases [7,8]. In the present study, we focused on whether pre-operative haematological parameters affected UCF development.…”
Section: Discussionmentioning
confidence: 96%
“…35 Recently, Demir et al showed that higher NLR values (1.16 ± 0.70) might predict renal scarring in patients with VUR, especially within the period of 3 to 6 months after the first attack of infection. 36 On the other hand, Zheng et al 37 also assessed the prognostic value of PLR in critically ill patients with acute kidney injury; they found that both low and high PLRs were associated with increased mortality. In our study, we also used hematological indices to define renal involvement in newborns with UTI.…”
Section: Discussionmentioning
confidence: 99%